System wczesnego ostrzegania jako element systemu wywiadu gospodarczego - Rzewuska, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article outlines issues of the early warning system of decision-makers. The author introduces premises of creating such a system in an enterprise and stages of forming it. The treated early warning system is a form of realizing the certain scope of function of the competitive intelligence. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 83-88